2012
DOI: 10.1063/1.3681146
|View full text |Cite
|
Sign up to set email alerts
|

Plasma resonances in a microwave-driven microdischarge

Abstract: This work investigates resonances in a capacitively coupled, low pressure krypton microdischarge operated at 2.5 GHz. A circuit model for the device, which has a length dimension of approximately 1 mm, calculates impedance values for a range of electron densities. The model results predict several “parallel” and “series” resonances at the driving frequency when the electron density is approximately 8 × 1011 cm−3 and 5 × 1012 cm−3. The series resonance occurs when the resistance approaches the output impedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
See 1 more Smart Citation
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
“…[3][4][5][6][7] Especially for several applications, such as medical instrument sterilization, metal surface nitriding, and high-velocity fuel ignition and combustion, atmospheric microwave plasma devices have shown its potential advantages in industrial applications. [8][9][10][11] There are four types of low-power microwave resonators: coaxial transmission line resonators (CTLR), 3 microstrip line resonators, 4 surfatron launchers, 12 and surface-wave plasma jets, [13][14][15] which are with different characteristics and thereafter are constructed for satisfying different application demands. Generally, these microwave resonators are excited by continuous microwave power supplies.…”
mentioning
confidence: 99%
“…The small size of the low-pressure microplasma devices, typically a few hundred microns, motivates the use of high excitation frequencies to limit the rate of loss of electrons and ions by drift in the electric field. In one configuration, a split-ring resonator operated at 2.45 GHz is used to create a large voltage across an electrode gap of a few hundred microns [7][8][9]. The use of arrays of split ring resonators to produce high pressure (up to atmospheric) microplasmas has been demonstrated by Hopwood et al [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…The series resonance occurs at a lower frequency related to the plasma frequency through a geometric factor involving the sheath thickness (s) and plasma length (L), x $ x p ffiffiffiffiffiffiffi s=L p . These resonant behaviors of the plasma have been intensively investigated over the years [3][4][5][6][7][8][9] (a brief chronological review is made in Ref. 3).…”
Section: Introductionmentioning
confidence: 99%